Poly-3,4-ethylenedioxythiophene/polystyrene sulfonate/dimethyl sulfoxide-based conductive fabrics for wearable electronics: elucidating the electrical conductivity and durability properties through controlled doping and washing tests - Aizamddin, Muhammad Faiz; Che Roslan, Nazreen; Ayub, Ayu Natasha; Mohmad Sabere, Awis Sukarni; Mohamed Sofian, Zarif; Yee, Hui Robin Chang; Mohd Ghazali, Mohd Ifwat; Sadasivuni, Kishor Kumar; Kasri, Mohamad Arif; Fakir, Muhamad Saipul; Mahat, Mohd Muzamir (2024)
Poly-3,4-ethylenedioxythiophene: polystyrene sulfonate (PEDOT/PSS) has revolutionized the field of smart textiles as an advanced conductive polymer, offering an unprecedented combination of high electrical conductivity, solution processability, and mechanical conformability. Despite extensive research in PEDOT/PSS-coated fabrics over the past decade, a critical challenge remains in finding the delicate balance between enhanced conductivity and washing durability required for real-world wearable applications. Hence, this study investigates the electrical conductivity and durability properties of PEDOT/PSS-based conductive fabrics for wearable electronics. By carefully controlling the doping concentration of dimethyl sulfoxide (DMSO), an optimal conductivity of 8.44 ± 0.21 × 10−3 S cm−1 was achieved at 5% DMSO. Durability was assessed through simulated washing tests of up to 30 cycles following standardized protocols. Although the fabric’s conductivity decreased from 10−3 to 10−4 S cm−1 after the 5th wash, it stabilized at approximately ~5.67 ± 0.05 × 10−4 S cm−1 beyond the 30th cycle. These findings demonstrate the fabric’s ability to retain its electrical properties under repeated washing, making it highly suitable for long-term use in wearable electronics. A range of characterization techniques—including attenuated total reflectance–Fourier transform infrared spectroscopy, Raman analysis, scanning electron microscopy–energy dispersive X-ray, X-ray diffraction, electrochemical impedance spectroscopy, and tensile testing—were employed to analyze the fabric’s functional groups, morphology, crystallinity, conductivity, and mechanical properties. The results validate the robustness and applicability of PEDOT/PSS/DMSO fabrics for reliable performance in wearable electronic applications.